Investiga????o da percep????o ambiental de alunos universit??rios no Brasil e em Portugal - Sobral, Eliane da Silva (2014)
Various academic fiels have been using studies related to perception to explain the various behavioral phenomena in face of the environmental and sustainability issues. Currently, in the researches related to social groups, there is a growing trend to understand the environmental behavior, due to the growing importance of the environmental issues mainly related to the disposal of waste, the use of fossil fuel and consumption of natural resources. The inclusion of sustainability issues into the means of spreading knowledge plays an important role in such a scenario. Therefore it is important to verify how such issues impact the behavior of university students in their personal, professional and academic life, and which are the impacts in their perception of the environmental problems. Aiming to investigate the Environmental Perception of university students from the Accounting Sciences Course in Brazil and Portugal. Based on the method of Survey, a structured questionnaire was created to get information about the perception of the students in relation to environmental issues. Afterwards, the data were analized based on constructs previously defined such as Social Demographic Inventory, Habits related to Sustainability, Practices in the University, and the understanding of Sustainability from the students which allowed to describe, understand and compare the attitudes, beliefs and concerns of the students that were investigated. The analysis comprised 441 university students in one Brazilian University (UNIVERSIDADE NOVE DE JULHO), and 138 students in 2 Portuguese Universities (UNIVERSIDADE DO MINHO E INSTITUTO POLIT??CNICO DE LEIRIA). For analysis between the two countries, 50 students from each school were selected so that it was possible to compare the schools. The results showed that the questionnaire, specially created for this study, was an efficient multidisciplinary tool to get data related to the environmental perception of university students. It was possible to identify, in general, that the students from both countries realize the importance of the environmental issues, but one can notice that thare little personal interest in getting knowledge about it to put into action in their professional market. Such incoherence, related to beliefs and attitudes was showed by the questions related to air pollution, preference for a mean of locomotion/transportation, to the consumption of sustainable products the selection of recyclable waste. As the questions related to consumption, it was noted that the economic factor is an important determinant for the environmental issues. Comparing the differences and similitudes of the perception of the environmental issues in Brazil and Portugal, it is showed that there is a considerable similarity between the subjects of both countries. Therefore, this paper contributes to the understanding of the perception of the undergraduate students about the environmental issues, for to enable the best approach to such issues in an academic environment, favoring the involvement of these individuals in actions for sustainability in their daily personal and professional.